Unraveling the Relationship Between Family-Supportive Supervisor and Employee Performance. (April 2013) - Wang, Peng; Walumbwa, Fred O.; Wang, Hui; Aryee, Samuel
This study examined the role of job satisfaction, relational identification with supervisor, and work-family conflict in explaining the influence of family-friendly supervision (FFS) on supervisor-rated citizenship behavior and task performance using data from a Chinese pharmaceutical company. Hierarchical regression analysis results revealed that job satisfaction mediated the relationship between FFS and supervisor-rated citizenship behavior, whereas relational identification with supervisor mediated the relationship between FFS and supervisor-rated task performance. We also found that work-family conflict moderates the relationship between FFS and job satisfaction. We discuss implications of these findings for theory and practice.